SANKSI PIDANA BAGI PELAKU KEJAHATAN SEKSUAL TERHADAP ANAK (PEDOFELIA) (Tinjauan Perspektif Hukum Positif Indonesia, Hukum Islam, Dan HAM Internasional) - Eli Suryani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Child is a surrogate of Allah, bud, potential, and the young generation, the successor of future goals of national struggle, has a strategic role, characteristics and special natures, so it must be protected from all forms of inhuman treatment. Among the forms of inhumane treatment is the sexual crimes, which resulted in violations of children's rights. In this case, for the perpetrators of sexual crimes on children, legal practitioners in Indonesia plan on giving emasculated punishment (as an additional punishment), in addition to the jail punishment. Observing the discourse (emasculated punishment), appears various respons, there are pros and cons. So that, before the law was enacted, the depth research would need to do, ensuring the pedofillia can be called a crime. What proposition is used. If no clear proposition found, what beneficiaries consideration is being used. If he devastating,what human element was ruined. If it is certain he is devastating and belived to be malicious it also necessary to know in which category of crime. After that, a suitable sanctions to the crime is set. To set it, a carefully, decompose and measurable data is a necessity